2015
DOI: 10.1167/iovs.15-17191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corneal Endothelial Dysfunctions on Intraocular Oxygen Levels in Human Eyes

Abstract: PURPOSE. We studied the implications of corneal endothelial dysfunctions on oxidative stress in the anterior segment via in vivo measurements of oxygen partial pressure (pO2) in the anterior chamber (AC) of human eyes. METHODS.We recruited 51 patients undergoing cataract surgery and/or endothelial keratoplasty (EK). Endothelial cell density (ECD; n ¼ 33) and central corneal thickness (CCT; n ¼ 41) were measured on patients with relatively clear corneas. Before surgery, an oxygen sensor was introduced into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…1 ). Furthermore, the O 2 concentration in the anterior chamber (5.4%) was confirmed to be within a safe range considering the short surgery time and the reported O 2 concentration in the aqueous humor in the human eye 24 .…”
Section: Discussionmentioning
confidence: 58%
“…1 ). Furthermore, the O 2 concentration in the anterior chamber (5.4%) was confirmed to be within a safe range considering the short surgery time and the reported O 2 concentration in the aqueous humor in the human eye 24 .…”
Section: Discussionmentioning
confidence: 58%
“…Using an oxygen‐sensing fiber optic probe inserted into the anterior chamber via a 30 gauge paracentesis, Siegfried et al () demonstrated in vivo that the partial pressure of oxygen (pO 2 ) in human aqueous humor differs consistently between the chamber angle, corneal subendothelial zone and posterior chamber. Furthermore, Huang et al () found a significant increase in aqueous pO 2 in the subendothelial region of patients with corneal endothelial dystrophy but no clinical evidence of corneal decompensation. This study hypothesized that dysfunctional CEC's utilize less oxygen than normal CEC's, resulting in increased subendothelial aqueous pO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the eye, PITX2 and FOXC1 mutations have also been shown to be associated with adult‐onset, rather than congenital, ocular disease. One such study by Huang et al () found that ∼11% of a large, adult glaucoma population coincidentally carried genetic mutations, including PITX2 and FOX1 mutations, otherwise responsible for anterior segment dysgenesis, microcornea, and microphthalmia, whereas Bailey et al () identified FOXC1 as a susceptibility locus for primary open‐angle glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…We have used a multilayered model cornea with an epithelium 50 m thick, a stroma 480 m thick, and an endothelium 2 m thick and with specific oxygen consumptions for each layer. We also use a value of 20 mmHg for aqueous humour oxygen partial pressure as found in recent studies [37][38][39][40] instead of 55 mmHg. 6,12…”
Section: Physiological Parametersmentioning
confidence: 99%
“…This has been an area of some discussion over the years. 40,[45][46][47][48] We note that, not only does stromal pO2 decline with anterior corneal surface pO2, but the stromal tissue exposed to very low (below 3-6 mmHg) pO2 values broadens.…”
Section: Model For Calculation Of Balance Flux Region (Xmin)mentioning
confidence: 99%